THE ROLE OF CIREUNDEU TRADITIONAL VILLAGE IN TOURISM MANAGEMENT - Satrio N. M.; Ahmad Hudaiby Galih Kusumah (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2022)
Traditional village is an area that is managed by a community with certain customary rules and has a strong relationship with the environment. These customary rules have the aim of maintaining the sacredness of the region and the culture that has been passed down from generation to generation. Cireundeu Traditional Village is one of many traditional villages in West Java, located in Leuwigajah Village, South Cimahi District, Cimahi City. The research, entitled "The Role of the Cirendeu Traditional Village in Tourism Management" aims to find out how effective the participation of indigenous peoples is in managing tourism in their area, especially in the Cirendeu Traditional Village. The results of this study are expected to enrich the repertoire of knowledge, especially those that can contribute to tourism in Indonesia. Based on the description, it can be concluded that the Cirendeu Traditional Village, which has a Sunda Wiwitan belief, can still survive with the beliefs and customs that have been passed down from generation to generation and take care of 3 forests, namely: the Prohibition Forest (Leuweung Larangan), Reforestation Forest (Leuweung Tutupan), Agricultural Forest (Leuweung Baladahan) very well which can be followed by how to take care of the forest which is very interesting to study and becomes a tourist attraction that can be explored philosophically for both local and foreign tourists.